Предмет:
МатематикаАвтор:
аноним9 1/5 - (5 * х - 4 1/2) : 11 1/4 = 8 14/15; (5 * х - 4 1/2) : 11 1/4 = 9 1/5 - 8 14/15; (5 * х - 4 1/2) : 11 1/4 = 46/5 - 134/15;(5 * х - 4 1/2) : 11 1/4 = 138/15 - 134/15;(5 * х - 4 1/2) : 11 1/4 = 4/15;(5 * х - 4 1/2) = 4/15 * 11 1/4; (5 * х - 4 1/2) = 4/15 * 45/4; (5 * х - 4 1/2) = (4 * 45)/(15 * 4); (5 * х - 4 1/2) = 3; 5 * х = 3 + 4 1/2; 5 * х = 7 1/2; х = 7 1/2 : 5; х = 15/2 * 1/5; х = 15/10; х = 3/2; х = 1 1/2. Проверка: 9 1/5 - (5 * 1 1/2 - 4 1/2) : 11 1/4 = 8 14/15;46/5 - (5 * 3/2 - 9/2) : 45/4 = 8 14/15;46/5 - (15/2 - 9/2) : 45/4 = 8 14/15;46/5 - 6/2 : 45/4 = 8 14/15;46/5 - 3 * 4/45 = 8 14/15;46/5 - 12/45 = 8 14/15;46/5 - 4/15 = 8 14/15;(46 * 3)/(5 * 3) - 4/15 = 8 14/15;138/15 - 4/15 = 8 14/15;134/15 = 8 14/15;8 14/15 = 8 14/15. Решение верно.
Автор:
lokiwyattДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть